The Notary's Responsibility for the Validity of Legalization of a Deed Under Hand Signed Without the Presence of the Parties (Case Study of Decision No. 146/PDT/2018/PT YYK) - Arkani, Fatmawaty; Masykur, Mohammad Hamidi; Harini, Novita Dian Phra (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
This research aims to examine the responsibilities of notaries in the legalization of private documents signed without the presence of the related parties. The primary focus is the analysis of Decision No. 146/PDT/2018/PT YYK, which highlights issues concerning the validity of the legalization of a land sale and purchase deed involving forged signatures. This study underscores Indonesian civil law regulations and the Notary Law (UUJN), which mandate that all parties involved in private documents must be present before the notary during the legalization process. The research adopts a normative juridical method with a conceptual, statutory, case-based, and comparative approach. The findings reveal that the legalization process conducted without the presence of all parties violates legal procedures and may compromise the validity of the document. Furthermore, the accountability of notaries who fail to comply with these procedures is not explicitly regulated under the UUJN or the code of ethics, creating potential risks for misuse. This study recommends the establishment of stricter regulations regarding sanctions for negligent notaries to ensure compliance with the law and protect the legal interests of all parties involved.